Interfaith dialogue between ethics and necessity – a study from the Qur’anic guidelines - Solihin, Sohirin Mohammad; Jassem, Layeth Suud; Osmani, Noor Mohammad; Shah Jani, Mohd.; Eeman, Muhammad Abbas (Canadian Center of Science and Education, 2013)
Muslim theology admits on diversity of faiths followed by mankind. The existence of religious diversity is aimed at, among other things, seeking a common ground in disseminating goodness and eradicating evil practices in the community. The study attempts to reveal the guidelines on religious dialogue from the passages of the Qur’an. The Qur’an emphasizes on the importance of communication and dialogue especially with the People of the Book. The Prophetic tradition also indicates on presence of other religious adherents. They are expected to work together in promoting goodness and establishing justice on the basis of divine precepts. Moreover, it highlights the importance of dialogue with different religious groups, as well as the prospect to wipe off misunderstandings that can lead into communal tension and crisis. The study will also shed light on the obstacles faced by religious leaders in conducting the dialogue and to contributing to the promotion of peace and justice. The most important part is that it attempts to expose the ethical guidelines as stated in the Qur’an which could be adopted as principles of dialogue. It is not aimed at condemning other faiths; rather it is aimed at exposing awareness on the differences and similarities which, in the long run, can give chance to restoring misconceptions.